2020
DOI: 10.3390/app10041333
|View full text |Cite
|
Sign up to set email alerts
|

Prediction System for Prostate Cancer Recurrence Using Machine Learning

Abstract: Prostate cancer is the fourth most common cancer affecting South Korean males, and the biochemical recurrence (BCR) of prostate cancer occurs in approximately 25% of patients five years after radical prostatectomy. The ability to predict BCR would help clinicians and patients to make better treatment decisions. Therefore, in this study, we have proposed a web-based clinical decision support system that predicts the BCR of prostate cancer in Korean patients. The data were obtained from the Korean Prostate Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Prior studies suggested several prediction models using various combinations of variables including initial PSA, greatest percentage of biopsy cores, number of positive biopsy cores, GS, and cancer stage for successful risk stratification, as well as oncologic outcomes including metastatic progression and prostate cancer-specific mortality following treatment [1,[16][17][18][19][20][21][22]. In our study, variables related to early BCR were in accordance with those in prior studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prior studies suggested several prediction models using various combinations of variables including initial PSA, greatest percentage of biopsy cores, number of positive biopsy cores, GS, and cancer stage for successful risk stratification, as well as oncologic outcomes including metastatic progression and prostate cancer-specific mortality following treatment [1,[16][17][18][19][20][21][22]. In our study, variables related to early BCR were in accordance with those in prior studies.…”
Section: Discussionsupporting
confidence: 86%
“…In order to predict patients with early BCR after RP, supervised learning algorithms, which mean classification methods, are used in a previous study of Lee et al [16]. Supervised learning algorithms analyze the characteristics of patients in two groups statistically, and based on these statistical differences, it can provide a prediction model that classifies patients with prostate cancer that are likely to experience BCR after RP.…”
Section: Prediction Of Early Bcr Using Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to develop a postirradiation recurrence prediction model using ML algorithms in PC carcinoma patients. This approach was previously used in order to predict the three-and five-year biochemical recurrence in PC patients initially treated surgically [27]. Also, one of the previous studies developed a model for the prediction of the presence of bone metastases, but this study had mixed early-stage cases with those who had advanced stage of the disease, and also both newly diagnosed patients and the ones who were previously treated [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these systems, namely clinical decision support systems (CDSS), are helpful tools for medical personnel to automate decision making and diagnose various health disorders with more precision. CDSS is widely used in certain medical fields, including the diagnoses of heart diseases [7][8][9][10], kidney diseases [11,12], diabetes [13,14], cancer [15,16], Alzheimer's disease [17], etc. CDSS are also applied in the field of geriatrics, where they are used successfully to assess signs of depression with an average accuracy of 95% [18] and diagnose dementia with a balanced accuracy of 82.3% [19], with an accuracy of 95.2% [20], and with an accuracy varying from 73% to 92% for various cases as presented in [21].…”
mentioning
confidence: 99%